Citra Tubuh pada Remaja Pengguna Instagram - Era Kurnia Aristantya; Avin Fadilla Helmi (Gadjah Mada Journal of Psychology (GamaJoP), 2019)
Adolescents are active social media user. There are various interactions  that happen in social media, social support is one of them. In Instagram, the interaction between users can be giving likes, comments, and sending direct messages. Meanwhile, high school adolescents (15—18 years old) have high preoccupation toward their body image. Thus, online social support is considered to have relationship with body image in adolescents Instagram’s user. The purpose of this research was to examine the relationship between online social support and adolescent’s body image. The subjects of this research were adolecents who lived in DI Yogyakarta, DKI Jakarta, Bandung, and Surabaya (n = 235). Body image was  measured using MBSRQ-AS (The Multidimensional Body-Self Relations Questionnaire-Appearance Scales) and online social support was measured using Social Support in Social Media Scale. The result of product moment analysis showed that online social support significantly correlated with adolescent’s body image (r = 0.261; p < 0.05). Further analysis found that there was body image difference between male and female adolescents (t = -2.104; p < 0.05). Age, location, access period, and the type of account followed did not have significant role on body image. In conclusion, adolescents need to have positive peer support.